Studi Genotipe Sitokrom P450 2A6 Alel CYP2A6*4 dan CYP2A6*9 pada Subyek Uji Perokok Suku Jawa Indonesia - CHRISTINE PATRAMURTI; FENTY FENTY (Fakultas Farmasi Universitas Pancasila, 2017)
CYP2A6 belongs to the CYP2 family of P450 cytochromes were highly polimorphy. CYP2A6*1 (wild type) was an active allele, CYP2A6*9 was agen decreased allele and the CYP2A6*4 was an inactive allele. By using the polymerase chain reaction technique (PCR), the CYP2A6 polymorphism was studied among Javanese Indonesian smokers. In the process of genotyping the CYP2A6*9 allele, some subjects who had been genotyped as CYP2A6*1/*4 in our previous studies were regenotyped as CYP2A6*9 in this study. The primer forward 2A6*9S and the primer reverse 2A6*9AS-wild type were used in these study. The Promega Go Taq Green Master Mix reagent were used to amplifl y the allele CYP2A6*1 in the positions at -395 to -28 of the CYP2A6 gene. The sample studied consisted of 20 smokers with Cigarrete per-Day (CPD) <10 and 13 smoker with CPD 11-20 from Javanese Indonesian population. In theses research, the subjects had been genotyped as CYP2A6*1/*4 in our previous studies. The allele frequencies of CYP2A6*1, CYP2A6*4, and CYP2A6*9 were 48.5%, 48.5%, and 3%, respectively. When these allele were considered simultaneously, among the subject, 63.9% were genotyped for CYP2A6*1/*4 and 6.1% were genotyped for CYP2A6*1/*4/*9. Based on the data collected, it could be concluded that the polymorphism of CYP2A6 among Javanese population sample study was not aff ected on smoking behavior.